Reviving Religious Moderation for World Peace from the Religious Moderation House in Indonesia - ., Masykur; Hermawan, M. A.; Masruri, Muhammad; J, Hasse (Journal of Ecohumanism, 2024)
Religious moderation was revived to mediate attacks on exclusivism and extremism that destroy human diversity. In the name of God, exclusivism and extremism continue to desecrate humanity. This paper describes the urgency of reviving religious moderation through the establishment of a house of religious moderation in three questions. Will the house of religious moderation contribute to a future of peace in Indonesia? How is the model of religious moderation practiced in the house of religious moderation? Why is religious moderation needed for world peace? With a multiculturalism perspective, the results of the study show that social recognition is an attitude that creates tolerance in religious moderation that contributes to the future of peace in Indonesia with the essence of religion to maintain human dignity. Its contribution can be seen in the practice of the religious moderation house which rests on the thoughts and movements of religious moderation. Thinking with values ​​(fair and balanced, cooperation, tolerance, compassion and kindness) and movement (nationality, tolerance, anti-violence and local culture) are models of religious moderation in Indonesia for world peace.